上顎埋伏乳臼歯を含む歯原性線維腫の1例 - 中村, 誠司; 清島, 保; 坂本, 瑞樹; 北村, 亮二; 川野, 真太郎; 松原, 良太 (日本口腔外科学会雑誌, 2018)
We report a rare case of odontogenic fibroma that included an impacted primary molar. The patient was an 8-year-old girl. Panoramic radiography and computed tomographic imaging revealed an apparently circumscribed, radiolucent lesion that was the size of the tip of the little finger and included the crown of the left primary second molar. Furthermore, a tooth-like radiopaque structure was located alveolo-palatally adjacent to the lesion. With the patient under general anesthesia, the lesion was removed along with the tooth-like structure and the impacted primary molar. The extirpated lesion was histologically diagnosed as odontogenic fibroma, and the tooth-like structure was diagnosed as odontoma. There has been no evidence of tumor recurrence after 2 years.